0152 Insomnia Severity and Daytime Complaints: What is to be Learned When These Domains are Discordant?. (27th May 2020) - Perlis, M L; Boyle, J T; Vargas, I; Giller, J; Seewald, M; D'Antonio, B; Muench, A; Williams, N J; Rosenfield, B; Klingman, K
Abstract: Introduction: If illness severity and daytime dysfunction are construed as categorical entities, it is possible to conceptualize the relationship between these variables in terms of a 2x2 matrix where the resultant cells represent a concordant dimension (quadrants 2 & 4 [high-high and low-low]) and a discordant dimension (quadrants 1 & 3 [high-low and low-high]). The question for the present analysis was, what percentage of subjects populate each quadrant and is it the case that the discordant dimension contains only a small percentage of subjects? Methods: Illness severity and daytime dysfunction data was collected from individuals with sleep continuity complaints in archival/community-based sample (N = 4680; 60% female; Ages 18–89) (www.sleeplessinphilly.com ). Illness severity was operationalized as Total Wake Time (TWT; [SL+WASO+EMA=TWT]) and daytime dysfunction was operationalized as the composite score of six daytime symptoms items. Median splits were calculated for each variable and subjects were typed accordingly (HH, LL, HL, & LH). Results: Surprisingly, the sample was relatively equally distributed into the two dimensions; 38% and 23% for the concordant dimension and 13% and 26% for discordant dimension. Conclusion: The 39% of subjects in the discordant groups might be thought of as complaining good sleepers (LH) and noncomplaining poor sleepers (HL). Other investigators have identified the LH subjects as individuals with "insomnia identity". Alternatively, it is possible to characterize the whole dimension as being related to a mismatch between the individual's sleep need and sleep ability. Those who need a lot, may suffer a lot, in the face of only a little (LH) whereas those who need a little, may suffer only a little, in the face of a lot (HL). Support: